Guidelines for Conducting Survey Research: Part 2 - Administration and Analysis. - Lyerla, Rob; Dirette, Diane Powers (Open Journal of Occupational Therapy (OJOT))
In the Fall 2024 issue of The Open Journal of Occupational Therapy (OJOT), the letter from the editor discussed the background of survey research and introduced the readers to a guideline for conducting research with a focus on survey development and recruitment of participants (Dirette & Lyerla, 2024). In this issue, we are following up with Part 2, which focuses on administering a survey and analyzing the results. We hope you find these guidelines useful for conducting quality survey research.